2000
DOI: 10.1148/radiology.216.2.r00jl06464
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Pulmonary Fibrosis: Cardiac Function Assessed with MR Imaging

Abstract: Impairment of right ventricular diastolic function was found by using MR imaging in patients with mild to moderate pulmonary fibrosis, whereas left ventricular diastolic function and biventricular systolic function were preserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…[71][72][73] Recently, a 'non-ischaemic' distribution pattern of hyperenhancement involving the right ventricular septal insertion points and the interventricular septum was described in patients with pulmonary hypertension 74 (Fig. 5B).…”
Section: Pulmonary Hypertensionmentioning
confidence: 99%
“…[71][72][73] Recently, a 'non-ischaemic' distribution pattern of hyperenhancement involving the right ventricular septal insertion points and the interventricular septum was described in patients with pulmonary hypertension 74 (Fig. 5B).…”
Section: Pulmonary Hypertensionmentioning
confidence: 99%
“…Impairment of the RV diastolic function (lower E/A ratio, corresponding to an abnormal relaxation pattern), with preserved LV diastolic filling and RV/LV systolic function was demonstrated early in the disease course of patients with mild-moderate collagen vascular disease related pulmonary fibrosis compared to healthy controls. 19 The functional and morphologic effects of pulmonary thromboendarectomy in patients with chronic thromboembolic pulmonary hypertension was assessed by Kreitner et al using a combination of three-dimensional (3D) Gd-contrast enhanced magnetic resonance angiography, cine-CMR and velocity-encoded CMR. 20 The study which included 34 patients demonstrated that 3D contrastenhanced magnetic resonance angiography performed equally as well as X-ray pulmonary angiography for the visualisation of segmental pulmonary vessels (533 out of 533 segments), was slightly worse for subsegmental vessels (681 versus 733 segments) but was superior for the depiction of the central origin of thromboembolic material.…”
Section: Pulmonary Hypertensionmentioning
confidence: 99%
“…IPF has also been associated with impaired right ventricular diastolic function, lower cardiac output [35], coronary artery disease [36] as well as acute coronary syndrome and deep-vein thrombosis [37], being possibly part of a systemic inflammatory process [36] involving the cardiovascular system. Such comorbidities could slow the recovery process [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…IPF has also been associated with impaired right ventricular diastolic function, lower cardiac output [35], coronary artery disease [36] as well as acute coronary syndrome and deep-vein thrombosis [37], being possibly part of a systemic inflammatory process [36] involving the cardiovascular system. Such comorbidities could slow the recovery process [35][36][37]. In addition, other causes of poorer longterm outcomes include abnormal pulmonary physiology from a smaller thorax in IPF [5], donor-recipient size discrepancy, remnant lung disease, severity of the disease as well as patient's operative fitness [32].…”
Section: Discussionmentioning
confidence: 99%